KOMPETENSI SUMBER DAYA MANUSIA (SDM) PADA OPERATOR PDDIKTI DI LLDIKTI WILAYAH XVI - Modjo, Sri Rahayu; Pakudu, Robin; Abdurrahman Idji, Rusly (Gapenas Publisher, 2024)
LLDIKTI Region XVI. The research method uses a qualitative approach with a descriptive type of research. The results of the study found that the Competence of Human Resources (HR) in PDDIKTI Operators in LLDIKTI Region XVI is not good enough and needs to be improved. Of the three indicators of the competencies used, all three have not been implemented properly. Regarding the knowledge indicator, most PDDIKTI operators have an adequate understanding of the system they manage, which is obtained through independent learning efforts and guidance from more experienced colleagues. However, there is limited knowledge on the DBMS aspect for some informants, especially at the leadership level, and there is still a lack of formal training that can support the competence of operators. The absence of technical guidance or special training for DBMS is one of the main factors that affect this limitation of expertise. Related to the skill indicator that PDDIKTI operators do not have sufficient expertise in operating DBMS effectively to support their work. The understanding of operators is generally still limited to specific areas of responsibility and is not comprehensive for all functions of the PDDIKTI system. Regarding the attitude indicator, the attitude of PDDIKTI operators towards their work responsibilities is quite good. They show motivation to perform tasks well despite challenges, especially in terms of great responsibility and data complexity. However, the aspects of work ethics and communication have not been implemented optimally, especially because there is no technical guidance that specifically discusses work ethics and communication.